Outcomes of autotransplant modifications after secondary alveolar bone grafting in patients with cleft lip and palate - Kyseliova, Н. В.; Yefimenko, В. П.; Tetruyeva, Н. А.; Holubchenko, О. І. (Actual Dentistry, 2024)
Purpose. This study aimed to evaluate changes in structural parameters of neoformed osseous tissue after the bone grafting alveolar process with different types of autografts. Methods. The analysis of the anthropometric indices of neoformed bone tissue was conducted by multispiral computed tomography scanning. 29 children with congenital clefts of the alveolar process aged from 8-17 years were involved in the survey. The autotransplant was used from the mandibular symphysis (I group) and tibia (ІІ group). Results. The overall success rate of the formed bone bridge in the I group was 66,6% and 57,9% in ІІ group (p = 0,632) according to the Bergland scale of complete regeneration. The average volume of the neoformed osseous tissue constituted in children of the I group stood at 71,0% ± 10,8, in the children of the ІІ group the defect filling appeared to be 68,9% ± 3,7 after 1 year. There was a statistically significant loss of bone volume in percentage equivalent between the I (1%) and II (9,9%) groups over the last 6 months (p = 0,008). During a year the density of the neoformed bone of the I group tended to get 526,1 ± 90,4 HU, in the ІІ group the average density was 288,0 ± 46,3 HU, this is 1,8 times less than in the I group (p = 0,054). Conclusions. It has been determined that the reparative processes and bone bridge formation of the mandibular symphysis autotransplant occur more rapidly during the first six months following grafting. At the end of the first year, the bone bridge’s volume and height parameters were similar, but the I group’s density remained higher than that of the II group.